Encyclopedia of Life Sciences 2015
DOI: 10.1002/9780470015902.a0002179.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia

Abstract: Neutropenia is a decrease in the number of neutrophilic leucocytes in the blood. Neutropenia is defined as an absolute neutrophil count or ANC (total white blood cells per litre multiplied by the percentage of neutrophils) more than two standard deviations below the normal mean. The ANC is usually more than 2.0 × 10 9 L −1 . Neutropenia is graded as mild, moderate or severe; severe is less than 0.5 × 10 9 L −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Neutropenia is caused by decreased neutrophil production, increased cell damage, bacterial and viral infections, drugs, administration of chemotherapy, and autoimmune diseases [19,20]. This is suits with the study of Qamar et al (2013) and Uplaonkar, which found neutropenia in 48 (32%) typhoid fever patients [21,22].…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Neutropenia is caused by decreased neutrophil production, increased cell damage, bacterial and viral infections, drugs, administration of chemotherapy, and autoimmune diseases [19,20]. This is suits with the study of Qamar et al (2013) and Uplaonkar, which found neutropenia in 48 (32%) typhoid fever patients [21,22].…”
Section: Resultsmentioning
confidence: 73%
“…Ishaq et al study (2020) found that 59% of typhoid fever patients experience eosinopenia [18]. Eosinophils are active primarily in the late stages of in ammation when antigenantibody complexes are formed and have the ability to phagocytose [19,20]. Eosinopenia is usually associated with the presence of an acute bacterial infection that usually causes fever.…”
Section: Resultsmentioning
confidence: 99%